The Impact of Training and Work Motivation on the Employee Performance: Evidence on Kampar Regency Inspectorate - Hayu Ardina; Supardi Supardi; Yusup Yusup; Wahyu Febri Ramadhan Sudirman (eCo-Buss, 2022)
This study aims to analyze the effect of training and work motivation on the performance of the Kampar Inspectorate employees. The data collection by distributing questionnaires directly to the Kampar Inspectorate employees using a purposive technique and obtained 63 respondents. Method analysis using a quantitative approach with multiple linear regression analysis. The finding indicate that the effect of training and work motivation simultaneously and partially has a positive effect on employee performance, this evidence showed that the training carried out by the Kampar Inspectorate and work motivation effectively improve the employee’s performance while the motivation has a stronger influence than training on performance. The findings demonstrate the implication for training and work motivation are importance to improving the employee performance and key role of increasing employee performance to be professional